Medición y evaluación en comunicación estratégica. Caso de estudio “Banco Solidario - Vega Ronquillo, Sofía Monserrath (2014)
The object of this investigation was to determinate how communication management contributed to reach the organizational objectives of Solidario Bank by the case study of “The New Brand Campaign”. For this purpose the Communication Management Bridge evaluation tool was applied, which consist on a close approach and investigation process within the organization; using the semi-structured interview conceived for every stage that this evaluation tool refers to. Data are relevant and its analysis remarks the importance of the communication evaluation process and the appropriate communication management models application in order to articulate the initiatives executed from this area. The results showed the contribution of this brand communicational campaign to the Bank mission and also the necessity of establish a communication politics that leads the communication management of this organization.